MICHEAL PORTER’S GENERIC STRATEGIES ON THE COMPETITIVE ADVANTAGE OF MSMEs IN THE FOOD INDUSTRY: A CUSTOMER PERSPECTIVE - K. P , Ezhil Maran.; Jeevarathinam, Dr. M. (South Eastern European Journal of Public Health, 2024)
Research aims: The main objective of the study is to explore the customers’ perception on Micheal Porter’s generic strategies in gaining a competitive advantage for MSME food enterprises. Design/Methodology/Approach: This study involves both primary data and secondary data. Primary data were collected using structured questionnaire from 280 customers of MSMEs food industry. Convenient sampling method was adopted to choose the respondents. Factor analysis and SEM were employed to analyze the data. Research Findings: The result of model measurement and AVE shows (CMIN=2.366, GFI=0.926, RMSEA=0.7) and (CA=0.67, DS=0.52, CP=0.69, LCS=0.59) which indicates a positive and strong relationship between customer perspectives and competitive advantage to the firm. Theoretical Contribution/Originality: The Porter’s generic strategies enhance the organizations competitive advantage through customers’ perception in terms of reliability, standard, reputation, growth and over all service. Practitioner/Policy Implications: Thus, low cost and differentiation strategy has positive effect on customer perception and as well offer competitive advantage to the firm’s Research Limitations: The study chosen MSME food enterprises located in Tambaram city only.